2021
DOI: 10.1016/j.jid.2020.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Extracellular Signal–Regulated Kinase/Ribosomal S6 Kinase Cascade Limits Chlamydia trachomatis Infection

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The influence-on-post-adsorption assay showed a significant inhibitory effect of rhein ( Figures 4B–D ). Our previous study demonstrated that the extracellular signaling-regulated kinase (ERK)/ribosomal S6 kinase (RSK) signaling pathway was important in C. trachomatis infection ( 46 ). To investigate the mechanism of action of rhein in C. trachomatis infection, the protein of ERK and RSK were performed by western blotting in the current study on C. trachomatis -infected cells treated with rhein for different times post-infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence-on-post-adsorption assay showed a significant inhibitory effect of rhein ( Figures 4B–D ). Our previous study demonstrated that the extracellular signaling-regulated kinase (ERK)/ribosomal S6 kinase (RSK) signaling pathway was important in C. trachomatis infection ( 46 ). To investigate the mechanism of action of rhein in C. trachomatis infection, the protein of ERK and RSK were performed by western blotting in the current study on C. trachomatis -infected cells treated with rhein for different times post-infection.…”
Section: Resultsmentioning
confidence: 99%
“…Rhein was previously reported to have effective antibacterial and antiviral activity against S. aureus, Helicobacter pylori , influenza A virus, and hepatitis B virus (HBV) ( 33 , 36 , 46 ). The mechanism of action of rhein was shown to involve direct impairment of pathogens or regulation of host cell signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Akt appears to be a more valuable upstream therapeutic target than Rab14 in persistent chlamydial infection. A recent study has demonstrated that several inhibitors of the ERK/RSK pathway represent potential treatment options for Host-directed therapy (HDT), limiting the development of Chlamydia ( Xue et al., 2020 ). Our study suggests that Akt inhibitors could also be a member of HDT, and help treat both acute and persistent chlamydial infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, further clinical studies are needed to determine the development of drug resistance and potential protective effects of gepotidacin in combination with doxycycline. 46 SiRNA knockout showed that Erk12 and RSK1 were important pathways for Chlamydia infection, and the first-class Erk12 inhibitor BVD-523, currently undergoing phase II clinical trials, inhibited Chlamydia infection in both cell cultures and mouse models; in other words, kinases in the Erk, RSK pathway may act as host-directed therapy CT. 47 A study 48 pointed out that systemic enzyme therapy can reduce the T H 2 cells, thus reducing the imbalance of local inflammatory processes and the formation of immune disorders, improving the effectiveness of antibiotic therapy and reducing the occurrence of adverse effects. The results showed that the clinical and microbiological response rates in CT infection patients were 97.6% > 78.6% with doxycycline and root enzyme combination therapy, compared with monotherapy (doxycycline), which were statistically significant (OR, 11.2; 95% CI, 1.3–247.9; P = 0.007).…”
Section: Infectious Factorsmentioning
confidence: 99%